The analysis of factors of telecommunications affecting market in RK (Journal of Economic Research & Business Administration, 2015)
In this article factors affecting market telecommunications and communication are considered. The branch of telecommunications and communication is a growing and binding segment of the Kazakhstan economy. Large-scale introduction of information and communication technologies has impact on increase in labor productivity and creation of conditions for progressive development of the domestic enterprises and their integration into world economy. At the present stage the main strategic competitors of JSC Kazakhtelekom in the market of services of the fixed telephony are mobile operators, and also operators of IP-telephony and, in particular, the Internet telephony. Having carried out the analysis of the market of a fixed telephony, it is possible to draw a conclusion that the market is saturated, namely life cycle of the market is at a stage of gradual recession. If there are prospects of growth of profitability, only at the expense of additional services. According to modern conceptual approaches to development of a market economy, communication serves as a core of a control system of economic processes. Experts consider that the economy which possesses the developed telecommunication branch, can be the worthy participant of world economic activity.
Keywords: Information and telecommunication technology; market of telecommunications; SWOT analysis; competitiveness of the telecommunication market; development factors